Resilience of Amalgamated Frameworks of Morality and the Law: Nigeria’s Road to Recovery - Jayeoba, Ayodeji (Advances in Social Sciences Research Journal, 2024)
There has, for about two centuries, been a whirlwind of controversies about the relationship between the law and morality, and whether morality should be legislated by national governments. In a typical African setting, there used to be no clear-cut distinction between law and morality before the colonialism and its system of government. Until lately in Nigerian communities, morality had as much force as the law. However, Nigerians’ attitude towards enforcement of morality and moral values has changed dramatically in recent times, so much so that as predicted by Dworkin, what used to be unthinkable and repulsive are fast becoming the norms. The 21st Century Nigeria is besieged by a variety of socio-economic and political problems such as terrorism and ethnic militia activities, widespread insecurity, poverty, hunger, homelessness, corruption and massively looting of public treasury. This paper explores such themes as the possibility of a nexus between decline in morality and the perennial socio-economic and political challenges of the contemporary Nigerian society and the law’s limitation and weaknesses in resolving the various challenges confronting the contemporary Nigerian state. It also examines the effectiveness of combining the frameworks of morality and the law in search of solutions to the challenges of contemporary Nigeria society.